Determinants of elite-level air rifle shooting performance - Ihalainen, S.; Kuitunen, S.; Mononen, K.; Linnamo, V. (Scandinavian Journal of Medicine & Science in Sports, 2015)
This study focused on identifying the most important factors determining performance in elite-level air rifle shooting technique. Forty international- and national-level shooters completed a simulated air rifle shooting competition series. From a total of 13?795 shots in 319 tests, shooting score and 17 aiming point trajectory variables were measured with an optoelectronic device and six postural balance variables were measured with force platform. Principal component analysis revealed six components in the air rifle shooting technique: aiming time, stability of hold, measurement time, cleanness of triggering, aiming accuracy, and timing of triggering. Multiple regression analysis identified four of those, namely stability of hold, cleanness of triggering, aiming accuracy, and timing of triggering as the most important predictors of shooting performance, accounting for 81% of the variance in shooting score. The direct effect of postural balance on performance was small, accounting for less than 1% of the variance in shooting score. Indirectly, the effect can be greater through a more stable holding ability, to which postural balance was correlated significantly (R = 0.55, P < 0.001). The results of the present study can be used in assessing athletes' technical strengths and weaknesses and in directing training programs on distinct shooting technical components.